Implementasi Islam Wasathiyah dalam Praktik Keagamaan Wahdah Islamiyah Kota Makassar - Dafid, Dafid; Ramli , Arif Rahman (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
The implementation of Wasathiyah Islam in religious practice has various styles, as does Wahdah Islamiyah. The main topic of discussion in this research is how Wasathiyah Islam is implemented in Wahdah Islamiyah religious practices. The research method used in this panel research is. The qualitative method aims to reveal the various uniqueness found in individuals, groups, communities and/or organizations in daily life in a comprehensive, detailed, deep and scientifically justifiable manner. The results of this research show that Wahdah Islamiyah's idea regarding Wasathiyah Islam is that Wahdah Islamiyah will always strive for unity without having to sacrifice the initial principles that have been established by religions and mass organizations, both in terms of aqidah, worship and muamalah and there are still many who think that Wahdah Islamiyah is a terrorist organization, extreme and exclusive because there are still many cadres and administrators of Wahdah Islamiyah who have not implemented the Islamic concept of wasathiyah as desired by Islam.